Modeling of Water Table Behaviour in District Ludhiana A Case Study - Madhusudan, Madhusudan; Khadatare, Y; Kaushal, M P (Journal of Agricultural Engineering, 2006)
There is a major emphasis on increasing the agricultural production in order to meet the increased food and fibre demand for increasing population of our country. In Punjab the surface water has almost been fully exploited and additional demand is being met by tube wells. During the period 1983-84 to 2002-03 the average rate of fall of water table was 18 cm per year. For efficient utilization and management, there is a need to predict the water table behaviour. A multiple regression model has been developed to predict the behaviour of water table based on area under paddy, wheat, total cropped area, rainfall and number of tube wells. The model fits well, having coefficient of determination (R2) 0.93 and the standard error 01’0.39. Close agreement was found between the observed and the model-predicted water levels.